Benefits of Digital Tools in Learning Evaluation - Ramadhan, Muhammad Qadri; Inayati, Nurul Latifatul (Jurnal Pelita Nusantara, 2024)
Significant changes in people's lifestyles and culture, especially the shift from print media to digital media, have forced the world of education to adapt quickly. Evaluation of learning in the digital era requires the development of learning strategies that utilize information and communication technology. Evaluation is crucial in understanding students' learning abilities and determining learning outcomes. Evaluation principles, such as continuity, completeness, cooperation, fairness, and practicality, are essential aspects of the evaluation process. Using digital evaluation tools, such as Google Forms and Kahoot!, has a positive impact with greater efficiency, effectiveness, and student engagement. Google Forms allows for more efficient evaluation by storing data in the cloud, while Kahoot! Provide a fun learning experience and increase student engagement. The workshop results showed that English teachers at SMA Negeri 1 Peranap positively responded to the use of Google Forms in evaluating digital learning, indicating acceptance and recognition of the benefits and convenience of this technology. Integrating digital evaluation tools is a relevant solution for improving the quality of learning in the digital era.